2022
DOI: 10.1186/s12879-022-07853-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus seroprevalence, infection, and disease in Chinese thoracic organ transplant recipients: a retrospective cohort study

Abstract: Background Cytomegalovirus (CMV) infection is a leading cause of morbidity and mortality after transplantation. This study aimed to investigate CMV seroprevalence, infection, and disease in Chinese thoracic organ transplant recipients. Methods The clinical data of the patients who underwent lung and/or heart transplantation between January 2015 and October 2020 were retrospectively collected from four transplantation centers in China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
1
1
1
Order By: Relevance
“…Furthermore, CMV infection is one of the most common opportunistic infections in these patients. A study carried out in China, with 308 post-pulmonary HTx patients, detected CMV in 52.3% of the sample 17 , while this study showed 44.9% and a median time of 39 days, that is, 50% of the population presented CMV within 39 days post-HTx.…”
Section: Discussioncontrasting
confidence: 67%
“…Furthermore, CMV infection is one of the most common opportunistic infections in these patients. A study carried out in China, with 308 post-pulmonary HTx patients, detected CMV in 52.3% of the sample 17 , while this study showed 44.9% and a median time of 39 days, that is, 50% of the population presented CMV within 39 days post-HTx.…”
Section: Discussioncontrasting
confidence: 67%
“…Além disso, uma das infecções oportunistas mais comuns nesses pacientes é a infecção por CMV. Um estudo realizado na China, com 308 pacientes pós-TxC e pulmonar, detectou CMV em 52,3% da amostra 17 , enquanto este estudo apresentou 44,9% e, ainda, tempo mediano de 39 dias, ou seja, 50% da população apresentou CMV em 39 dias pós-TxC.…”
Section: Discussionunclassified
“…Pathogen evidence was based on comprehensive microorganism detection methods, which included mNGS, culture, and smear. Furthermore, the diagnosis of Cytomegalovirus (CMV)infection was made based on established guidelines and our prior study [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%